PERAN SULTAN ABDUL HAMID DALAM MENJALANKAN POLITIK DAGANG BEBAS DI KESULTANAN BIMA TAHUN 1773-1817 - Asmawati, Asmawati (Universitas PGRI Yogyakarta, 2021)
This study aims to determine the history of free trade politics at the time of Sultan Abdul Hamid, as well as its impact on the socio-economic community of Bima. The method used is literature review, with several stages including; a) title selection, b) heuristics, c) source criticism, d) interpretation, and e) historiography. The results showed as follows: 1) Sultan Abdul Hamid was the 9th Sultan of Bima, he was born around 1761 and died on 1 Ramadan 24 June 1819. 2) The efforts made by Sultan Abdul Hamid in carrying out free trade politics in Bima were: a) The Sultan was on good terms with the Netherlands, b) the advantage of the dissolution of the VOC due to rampant corruption, c) the Dutch lost to the British which automatically Bima was under British rule, d) the attitude of the Sultan and Ruma Bicara were disloyal to the contents of the agreement with the Dutch, 3) The impact felt by the community after being released from the Dutch trade monopoly was not that long, due to the eruption of Mount Tambora in 1815.